Integrasi Fiqh Munakahat dalam Kurikulum Pesantren: Studi Atas Kitab Tuhfah al-Rāghib dan Praktiknya: Integration of Munakahat Fiqh in the Islamic Boarding School Curriculum: Study of the Book of Tuhfah al-Rāghib and its Practice - Dzafitri Fadhli Robbi; Khilawatul Jamil; M. Ahsin Miftahudin (DIRASAH: Jurnal Kajian Islam, 2026)
This study examines in depth the integration of fiqh munakahat (Islamic jurisprudence) into the Islamic boarding school curriculum, focusing primarily on KH. Musta'in Nasoha's book, Tuhfah al-Rāghib fī Syarḥ al-Taqrīb (The Book of Tuhfah al-Rāghib fī Syarḥ al-Taqrīb). As a Shafi'i fiqh work, this book not only outlines the normative aspects of marriage law but also teaches ethics, morality, and family responsibilities. This research uses a qualitative approach with a case study. The results show that this book is integrated through classical learning methods such as bandongan (the discussion of the Islamic jurisprudence), sorogan (the discussion of Islamic jurisprudence), and marriage contract simulations. The values contained in this book have proven relevant in addressing modern issues such as the digitalization of social relations, the culture of consumer dowries, and domestic conflicts among the younger generation.